Fire history and climate-growth response of Abies spectabilis : A case from Langtang National Park, Nepal Himalaya - Basnet, S.; Gaire, N. P.; Chhetri, P. K. (Banko Janakari, 2019)
This study presents the potential of a conifer species (Abies spectabilis D. Don) to reconstruct fire history by using dendro chronological technique along with thedendroclimatic response in Langtang National Park, Central Himalaya of Nepal. For the fire history reconstruction, altogether eight cross-sections samples from fire affected eight trees and another 20 tree-cores from 10 trees with visible fire scars were taken. In the case of dendroclimatic study, 24 healthy cores of A. spectabilis were selected from the 40 cores extracted from 19 trees. The standard dendro chronological methodology was used for sample preparation and analysis. A 199-year long ring-width chronology of A. spectabilis spanning from 1818 to 2016 AD was developed. In spite of visible fire burn in near bark-surface, no potential fire scars are seen in inner parts in the cross-section samples. However, 12 cores showed that three fire burns occurred simultaneously in the forest area in the years 1917−1918, 1969−1970 and 2009−2010, respectively. Tree-ring-based fire event-record is found to be concurrent to the local people's perceptions/experience about the past fire history in the area. Tree growth climate relationship showed sensitive responses to both growing and non-growing season’s temperature and precipitation variability. Summer temperature had positive influence on growth of the species. Precipitation of monsoon and autumn were found to have negative influence on radial growth whereas pre-monsoon precipitation had positive association with tree radial-growth. This preliminary assessment shows that there is a huge potential of tree-ring research for long-term fire history in the region and helps us to better understand the role of fire in the ecology and management in the Himalayan region. The study can also be replicated in other fire-affected areas of the Himalayan region by using fire sensitive species in the sampling.